PROBLEMS OF THE IMPLEMENTATION OF EU LABOUR LAW IN POLAND - Ludwik, Florek (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
Before the accession to the European Union (May 2004) Poland implemented all directives of labour law. The paper presents problems and difficulties of the implementation and application of EU labour law in Poland. It concerns, in particular the equal treatment of employees, employment for a specified period, temporary employment, transfers of undertakings, businesses or parts of undertakings or businesses, mass redundancy (group layoffs), informing and consulting employees and partially working time with special regard to doctor's situation. The highlighted problems are connected with different provisions and institutions of Polish labour law based on a national legal tradition. Some problems of implementation have been the consequence of still different economic situation as compared with old European countries. They have been also resulted from different industrial relations in Poland, especially the lack of collective bargaining on the above-undertaking level. Some problems have been related to other Polish international obligations, especially ratified International Labour Organization conventions. Some troubles have caused the way of translating and implementing the EU labour law directives in Poland. Keywords : European Union, labour law, equal treatment of employees, mass redundancy.